Carbon-scaled nitrous oxide emissions better reflect the impacts of land use changes than raw nitrous oxide emissions in the Dry Chaco region - Chalco Vera, Jorge Elías; Acreche, Martin Moises (Elsevier, 2024)
In the Dry Chaco region, agriculture expansion has caused significant land use change hotspots. However, the post-impact of land use change on nitrous oxide (N2O) emissions and carbon (C) budgets remains unknown. This study aimed to contrast the impacts of the main land use systems on N2O emissions related to its C inputs and C budgets by comparing them with those of a native forest at two sites of the Dry Chaco region of Argentina. At Site 1, the land use system were soybean-fallow-soybean and maize-fallow-maize sequences, whereas at Site 2, it was a soybean-wheat sequence. Measurements of soil N2O and carbon dioxide (CO2) fluxes were carried out monthly using the static chamber method. The C budgets of each system were determined for the annual crop-fallow cycle by the difference between the C inputs (from annual aboveground (ABG), belowground (BG), and rhizodeposition) and C outputs (defined as cumulative CO2-C emissions). At Site 1, the native forest showed 168 and 50 % more cumulative N2O emissions than maize and soybean, respectively. However, most land use differences were based on C inputs. Thus, when the cumulative N2O emissions of each system were related to their C inputs, the N2O emissions per ton of C entered of the native forest were lower than those of soybean and similar to those of maize. The C budgets (± standard error) at Site 1 were 6.4 ± 1.3, 1.0 ± 0.3 and −0.7 ± 0.6 t C ha−1 yr−1 for native forest, maize and soybean, respectively. At Site 2, they were 3.1 ± 0.7 and −4.0 ± 0.6 t C ha−1 yr−1 for the native forest and the soybean-wheat sequence, respectively. This paper proposes a comprehensive approach that integrates C inputs and budgets when evaluating N2O emissions from different land uses as a guide to define mitigating management practices and considers a native vegetation system to unmask the real impacts of agroecosystems.